UV-B induced flavonoid accumulation and related gene expression in blue- grained wheat at different periods of time - Li, Li; Jiang, Guofei; Li, Hanxue; Liu, Junna; Zhang, Ping; Wang, Qianchao; Huang, Liubin; Zhang, Shan; Wang, Xuqin; Zhang, Lingyuan; Bai, Yutao; Qin, Peng (Frontiers in Plant Science, 2024)
UV-B can be used as an additional technique for nutrient accumulation in blue-grained wheat, which has special nutritional properties due to its blue starch layer. The concentration of flavonoids in blue-grained wheat under UV-B irradiation is extremely important for further investigation and exploitation of the nutritional properties of blue-grained wheat. This investigation focuses on the expression of flavonoids and associated genes in blue-grained wheat using transcriptomic and metabolomic analyses. The metabolome revealed 1846 compounds and 340 flavonoids after UV-B irradiation. Under UV-B irradiation, the amount of flavonoid metabolites decreased over time, but flavones and flavanols increased, and flavones and flavanols were more diverse and abundant. The content of some flavonoids of blue-grain wheat in period 2 was significantly higher under UV-B irradiation than its check and other periods of different treatments. There are 42344 differentially expressed genes identified from trascriptomic analysis, including 151 genes associated with the flavonoid pathway. The genes for the enzymes FLS, ANR, HCT, CYP75A and CYP73A are more abundant, with F3H and FLS showing higher expression levels. The expression of these genes decreased after early UV-B irradiation, but increased later. In the joint WGCNA study of the two groups, the FLS enzyme gene LOC123125079 plays an important role in the response of blue-grained wheat to UV-B irradiation. Our findings help to identify essential genes and processes that allow blue-grained wheat to respond appropriately to UV-B irradiation, which is critical for the accumulation of flavonoids and other bioactive compounds in coloured wheat, maximising its nutritional properties.